Physical characterization of frozen fruits from eight cultivars of the North American pawpaw (Asimina triloba) - Adainoo, Bezalel; Crowell, Brendan; Thomas, Andrew L.; Lin, Chung-Ho; Cai, Zhen; Byers, Patrick; Gold, Michael; Krishnaswamy, Kiruba (Frontiers in Nutrition, 2022)
Pawpaw (Asimina triloba [L.] Dunal) is an underutilized fruit native to North America. The fruit has a short shelf life, and browns and softens rapidly after harvesting. These characteristics present a challenge to the advancement of pawpaw as an economically viable specialty crop. This study evaluated the physical characteristics of frozen fruits from eight cultivars of the pawpaw fruit to establish the processing potential of pawpaw fruits. The results show that freeze-thaw cycle may have influenced the peel thickness, peel color, and pulp color of the fruits. Fruits of the Susquehanna cultivar had the highest fruit weight and pulp weight, making them potentially the most suitable for pulp processing. The pawpaw fruits had almost neutral pH ranging between 6.07 ± 0.21 and 6.47 ± 0.11, which could contribute to the rapid browning on exposure to air since an acidic pH is important for slowing enzymatic browning. To aid pawpaw juice extraction, enzymatic treatments may be necessary to increase the juice yield from the pulp. Overleese fruits may be the best for pawpaw juice production. These findings can aid in the selection of processing equipment and guide processors in their efforts to utilize pawpaw fruits to avoid postharvest and post-processing losses.